Effect of self-cementing properties on the mechanical behaviour of recycled concrete aggregates in unbound pavement layers - Wang, Chong; Chazallon, Cyrille; Jing, Peng; Hornych, Pierre; Latour, Benjamin (Transportation Geotechnics, 2023)
International audience Recycled concrete aggregates (RCA) are increasingly being used in pavementbase and subbase layers to replace the natural unbound granular materials (UGM), while theinfluence of their self-cementing properties on the mechanical behaviour has not beenthoroughly studied. In this paper, the self-cementing properties, permanent deformation andresilient deformation behaviour of two RCA, NRCA and ORCA, showing significantlydifferent self-cementing properties, after curing for different times (1, 180, 360 and 720 days),were investigated by pH value measurements, calorimeter tests and repeated load triaxial tests(RLTT). The results show that the self-cementing properties can significantly improve themechanical behaviour of RCA, which is comparable to that of lightly treated materials. Thepermanent deformations of NRCA, showing strong self-cementing properties, decreases to avery low value quickly after curing for 180 days, and then stabilizes. While the resilientmodulus of NRCA increases continuously with curing time, up to the studied curing time (720days), 4.3 times larger than that curing for 1 day. It was also found that the traffic loads candamage the bonds between particles formed due to the self-cementing properties. On thecontrary, for ORCA, showing negligible self-cementing properties, curing has no influence onthe mechanical behaviour.